Tradisi Massulakka ke Kotak Amal Imam Lapeo: Sebuah Resepsi Kenabian - Makmur Makmur; Syarif Abbas; Muhammad Ismail (Institut Agama Islam Negeri Kendari, 2022)
Alms is one of the prophetic teachings that can be seen in various text books of the Prophet’s hadith sources. The reception of the meaning of hadith which is actualized by Muslims with various religious practices is referred to as living hadith. One of them is the massulakka tradition to the Imam Lapeo charity box which is located on the side of the Trans-Sulawesi road, Nuruttaubah Lapeo mosque, Lapeo Village, Campalagian District, Polewali Mandar Regency, West Sulawesi Province. The research method is qualitative based on the results of interviews and observations. The main speakers were Imam Lapeo's grandchildren and great-grandchildren, Annangguru Hisham and Annangguru Zuhriah. Meanwhile, the sources of the experience of the massulakka community were taken in a random from the Polewali Mandar community, a total of 20 people from outside the region. This research is also based on library data such as books, journals and social media data. The approach used is the living hadith, while the analytical model uses reception theory and Shutz’s motivation theory, namely because of motive (past causes) and in order of motive (future causes). The result of his research is that the massulakka tradition is a living hadith phenomenon which is motivated by the figure of Imam Lapeo who teaches alms as the teachings of the Prophet. The benefits of giving charity become evident in the person of Imam Lapeo in the form of hospitality such as getting safety and spaciousness of sustenance. After death, the community as the in-order motive in carrying out the massulakka tradition to the charity box at the Imam Lapeo location has the motivational goal of being able to resist reinforcements, invite sustenance, calm the soul. The proceeds from the charity box are used for the benefit and development of Islamic society such as the empowerment of mosques and orphanages managed by the administrators of the Lapeo Nuruttaubah Mosque. Theoretically, the use of Shutz’s theory of motivation is relatively new in Living Hadith, so this research adds to the discourse on the need to build a solid theoretical episteme in the study of Living Hadith